Biological management of Sclerotinia sclerotiorum in pea using plant growth promoting microbial consortium. (2nd March 2015) - Jain, Akansha; Singh, Akanksha; Singh, Surendra; Singh, Harikesh Bahadur
<x xml:space="preserve">Abstract</x> The beneficial plant‐microbe interactions play crucial roles in protection against large number of plant pathogens causing disease. The present study aims to investigate the growth promoting traits induced by beneficial microbes namely Pseudomonas aeruginosa PJHU15, Trichoderma harzianum TNHU27, and Bacillus subtilis BHHU100 treated singly and in combinations under greenhouse and field conditions to control Sclerotinia sclerotiorum. Plants treated with three microbe consortium enhanced plant growth maximally both in the presence and absence of the pathogen. Increase in plant length, total biomass, number of leaves, nodules and secondary roots, total chlorophyll and carotenoid content, and yield were recorded in plants treated with microbial consortia. Also, a decrease in plant mortality was observed in plants treated with microbial consortia in comparison to untreated control plants challenged with S. sclerotiorum. Furthermore, the decrease in disease of all the treatments can be associated with differential improvement of growth induced in pea.